Blackstone's guide to the Civil Justice Reforms 2013 - Sime, Stuart; French, Derek (Oxford University Press, 2013)
The only practical guide to the procedural reforms due to be implemented in April 2013 which give effect to the wide-ranging recommendations made by Sir Rupert Jackson in his Review of Civil Litigation Costs (MoJ, 2009) dealing with the costs of civil litigation.